Legal regime of matrimonial assets - Melnichenko, Oksana V. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article deals with the difference between the categories of "common property " and "community property (assets)", its practical importance in the division of matrimonial assets, maintenance of law and order through the mechanism of the legal regulation in general and as a part of the mechanism - the legal regime of property, and – the components of the legal regime of matrimonial assets.